Endometrial Cancer: Aberrations in Signaling Pathways and Targeted Intervention - Yadav, Ritu; Ahuja , Parul; Lathwal, Nancy; Chauhan, Preeti (Challenges and Advances in Pharmaceutical Research Vol. 10, 2022)
Endometrial carcinoma is the most common form of uterine cancer that has been adding more than four lakh cases annually to the list of gynaecological cancers, with high economic countries spiking up the pace. However, developing countries, including India, also show a significant number of cases. As this anomaly is associated with excessive estrogen- obesity, PCOD, estrogen-secreting tumors, menarche at an early age and menopause at a late age are some of the major risk factors contributing to its cause. Changes at the genetic level and deteriorated signaling pathways pave the way for the development of endometrial cancer. Alterations in PI3K/PTEN/AKT pathway have been implicated primarily in TYPE I of endometrial cancer, whereas the main altered pathway responsible for TYPE II is p53/p16 pathway, among others. Various treatment strategies targeting these particular signaling pathways are in different phases of trials, and some have shown promising results too. So, developing targeted therapies based on specific molecular pathways would aid in a good response rate and better prognosis for endometrial cancer patients.